Existence of Research Based Learning Model: Method Improving Knowledge Asimilation - Indah Lestari; Noer Saudah; Catur Prasatia Lukita Dewi (Health Notions, 2022)
Models of learning and creative thinking ability are important factors that must be considered in improving student learning outcomes. The research development aims to develop research-based practice learning models to improve learning achievements in the development of assimilation and application of student knowledge. The study was conducted on undergraduate Nursing students who were carrying out the clinical practice. The method in this study was the Research Development (RD) method and the second stage was the RBL model trial. The development of RBL models in this study began with the preparation of models, expert tests, empirical tests on practical students, and continued empirical tests on students. Then the model was improved and the final product was determined (final model). Students are involved in the implementation of learning and learning reflection. This research involved 500 students. Data was collected using a student rating or self-evaluation scale consisting of 27 items. The analysis technique used  Partial Least Square (PLS). Research output is research-based practice learning models. Research-based learning can improve students’ skills in solving problems, thinking critically, scientific work skills, the mastery of physics concepts, students’ generic abilities, the science process skills in physics, and students’ science literacy. Keywords: research based learning; practice learning; knowledge